Falls in HIV-Infected Patients: A Geriatric Syndrome in a Susceptible Population. (July 2013) - Ruiz, Marco Andres; Reske, Tom; Cefalu, Charles; Estrada, John
Background: Falls is a common geriatric syndrome that has not been well characterized in HIV-infected populations. Methods: We retrospectively reviewed our database and identified patients who fell over the last 12 months. Results: Thirty-two patients were identified (incidence rate of 16 × 1000 patients per year). Twenty-five percent were female and 75% male. Sixty-seven percent were African American with 33% Caucasians. Average age was 48.19, number of years with HIV infection on average was 9.38 years, mean CD4 count 347.2 cell/mm 3, mean HIV viral load was 31 379 copies/mL. The average number of medications was 8.7 with a mean of 3.48 comorbidities. The mean vitamin D level was 27.20. Sixty-two percent of patients were compliant with antiretroviral therapy. Univariate and multivariate analysis showed that number of medications (< .005 medications; P < .005), more than 3 comorbidities ( P < .005), and noncompliance ( P < .001) were related to falls in this population. Conclusion: Falls is a common geriatric syndrome. Associated risk factors in our cohort included number of medications, more than 3 comorbidities, and noncompliance. Larger studies are needed to properly characterize this geriatric syndrome in HIV-infected patients. As HIV-infected populations age, a shift into a more comprehensive geriatrics care including fall risk evaluation may be needed.